A Simple Survey on Attitude of Computer Science Diploma Students towards STEM - Azniah Ismail; Nor Zuhaidah Mohamed Zain; Harnani Mat Zin (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
This article reported a simple survey on diploma students’ attitudes towards science, technology, engineering, and mathematics (STEM) objectively to get an initial impression of students taking a STEM-related diploma program. The targeted respondents were diploma students pursuing computer science programs in a Malaysian public university. A quantitative approach using a quantitative survey was used in which data were systematically elicited from 16 male and 17 female students using a questionnaire containing Likert-scale items. The questionnaire consists of three constructs: attitude toward science, attitude toward technology and engineering, and attitude toward mathematics. All constructs use a 5-point Likert scale for the response scale. Descriptive analysis showed that the respondents’ attitude ranged between moderately to highly positive towards STEM with no significance different variation between genders across the STEM fields. Interestingly, they also had, generally, moderate consideration for careers in STEM fields (the average values ranged between 27.2% and 42.4%) with male respondents had very low agreements (18.7%) to consider careers related to technology and engineering fields. Such results were a bit discouraging as the respondents were all pursuing a diploma in computer science.Thus, more efforts are needed by the university to give more exposures and experiences to refine the students’ attitude during their study, to boost their confidence and interest to pursue a career suitable with their diploma certificates.